Sri Lanka : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper on Sri Lanka provides background information on economic developments and on selected policy issues facing Sri Lanka. The main economic developments in 1996 and the first quarter of 1997 are discussed. The paper highlights that in 1996, a severe drought, power shortages, and an escalation in the military conflict contributed to a sharp deterioration in the economic situation. With the end of the drought and power shortages, and a rise in investor confidence, macroeconomic conditions in 1997 were more favorable.